Are the information needs of parents being met regarding their child's oral chemotherapy?. Issue 6 (9th May 2013) - Kinsella, A; Alldred, D; Waite-Jones, J
Abstract : Aim: The emphasis on delivering personalised care tailored to meet the needs of patients has been at the forefront of UK government health policies for a number of years. 1 However, before we can meet the needs of patients, their needs need to be identified and explored. For parents of children on oral chemotherapy, it is paramount that they fully comprehend what they are required to do in order to safely and effectively manage the oral chemotherapy at home. This study aims to identify, explore and analyse the information needs of parents regarding their child's oral chemotherapy to enable the future provision of high-quality individualised information. Method: A qualitative methodology was used; semi-structured interviews were conducted with parents regarding their child's oral chemotherapy. A diverse sample of parents was purposively chosen to encompass children at different stages of treatment and with different diagnoses. Interviews were audio-recorded and transcribed alongside field notes made by the interviewer. Data were analysed using thematic analysis. Results: Thirteen parents (12 mothers; one father) were interviewed. Two overarching themes were identified; the need for information and the parental struggle. Parents were found to have a wide variety of information needs ranging from treatment related information to information on drug-food/drug-drug interactions. Despite differences in the type of medicines related information parents required, all parents expressed the need for reassurance on aspects of their child's treatment. Most of the parents preferred to receive verbal and written information on the oral chemotherapy, with two parents suggesting the internet as an additional source of information. Although all parents indicated they were satisfied with the information provided to them by the healthcare team, a number of unmet needs were identified. These included how to safely handle the oral chemotherapy and basic details about the drug, what it is and how it works. Parents encountered many difficulties at home such as dealing with the side effects of treatment and administering the medicines whilst trying to maintain normality for the family. Even though the majority of parents felt overloaded with information and struggled with the quantity of information provided, parents often sought further information from additional sources (eg, internet) for reassurance. Conclusions: Information needs varied between parents but also at different stages of the disease pathway. Although the need for treatment related information was expressed by parents, the need for practical information, support and reassurance in connection with their coping strategies was fundamental to managing their child's cancer day to day. As a result of this study, the wording on the oral chemotherapy patient information leaflets has been changed to reflect issues highlighted. A medicines administration chart template and a bullet pointed do's and don'ts list regarding the oral chemotherapy are currently in development; these aim to further support parents in managing the oral chemotherapy at home.